Dynamic interconnectedness and portfolio implications among cryptocurrency, gold, energy, and stock markets: A TVP-VAR approach - Amirreza Attarzadeh; Mugabil Isayev; Farid Irani (Sustainable Futures)
This article assesses the temporal and dynamic interconnectedness of cryptocurrency, gold, energy, and stock markets, essential for portfolio diversification. Using a TVP-VAR model, we analyze the return and realized volatility from November 11, 2013, to August 22, 2022. The study focuses on Bitcoin, gold, and renewable energy dynamics. Findings show that volatility shocks are most significant in the crude oil market, while Bitcoin's relationship with other assets is weak during non-crisis periods. Gold and Bitcoin's connection is less pronounced during crises. These results provide insights for portfolio optimization in both crisis and non-crisis periods.